Bantuan Perencanaan Renovasi Pos Keamanan Lingkungan Perumahan Bumi Wanamukti Kelurahan Sambiroto, Kecamatan Tembalang, Kota Semarang - shifa fauziyah (Jurnal Pengabdian Vokasi, 2023)
Bumi Wanamukti Residential is a housing complex located in Tembalang District. The Poskamling in the housing estate was badly damaged, so it could not be used. Citizens plans to improve the security infrastructure by renovating the existing poskamling. This community service aims to help housing residents to renovate poskamling in the form of technical consultations assistance before and during construction. Methods of construction the activities carried out includes: the process of designing the poskamling building structure, calculating  and the monitoring process during its construction. With the renovation of the Poskamling development, it can be used for patrol activities, more security guards comfortable in Bumi Wanamukti Residential.